Pengelolaan Pertanian Karet Ditinjau Dari Kompilasi Hukum Ekonomi Syariah - Ahmatnijar, Marlina Siregar & Syafri Gunawan & (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2021)
The formulation of the problem in this study is how the implementation of muzara’ah cooperation in the village of Muara Purba Nauli, sub-district of Angkola Muaratais and how to review the Compilation of syariah Economic Laws on the implementation of muzara’ah cooperation in Muara Purba Nauli village, Angkola Muaratais district.The method used in this research is to use descriptive qualitative methods. The system in this research is carried out by collecting primary data and secondary data. The results of the implementation of cooperation in the management of rubber agricultural land canceled in there is a deviation made by the cultivator or violates the agreed agrement. As happenedin the village of Muara Purba Nauli, Angkola Muaratais subdistrict in the cooperation of Rubben Land Agriculture, such as planting cacao trees in the land, without the knowledge of the land owner and making in their property, resultingin irregularities in the cooperation of this rubber land, plus openness. The tenants do not exist with the land owners. The implementation was in accordance with the contract stated in general, as for the planting of cacao trees by rubben farmers that were not explained during the contract. But if it is based on Islamic rules, or the compilation of Islamic economic law has ended because it has violated the cooperation agreement in accordance with Article 218 paragraph 1.